MUC4 expression is a novel prognostic factor in patients with invasive ductal carcinoma of the pancreas. Issue 8 (27th July 2005) - Saitou, M; Goto, M; Horinouchi, M; Tamada, S; Nagata, K; Hamada, T; Osako, M; Takao, S; Batra, S K; Aikou, T; Imai, K; Yonezawa, S
Abstract : Background: Many patients with invasive ductal carcinoma of the pancreas (IDC) have a poor outcome. MUC4 expression has been implicated as a marker for diagnosis and progression of IDC, but there are no studies of the relation between MUC4 expression and patient prognosis in IDC. Aims: To investigate the prognostic significance of MUC4 expression in IDC. Methods: The expression profiles of MUC4, ErbB2, p27, and MUC1 were investigated in IDC tissues from 135 patients by means of immunohistochemistry. Results: MUC4 was expressed in 43 of the 135 patients with IDC (31.9%). The survival of 21 patients with high MUC4 expression (>20% of neoplastic cells stained) was significantly worse than that of the 114 patients with low MUC4 expression (<20% of neoplastic cells stained) (p = 0.0043). Univariate analysis showed that high MUC4 expression (p = 0.0061), large primary tumour status (>T2) (p = 0.0436), distant metastasis (p = 0.0383), lymphatic invasion (p = 0.0243), and surgical margins (p = 0.0333) were significant risk factors affecting the outcome of patients with IDC. Backward stepwise multivariate analysis showed that MUC4 expression (p = 0.0121), lymph node metastasis (p = 0.0245), and lymphatic invasion (p = 0.0239) were significant independent risk factors. ErbB2, p27, and MUC1 were not independent risk factors. Conclusions: This study shows that MUC4 expression in IDC is a new independent factor for poor prognosis and predicts the outcome of patients with IDC.